First documented reinfection of SARS-COV-2 in second wave from Pakistan - ul Haq, Zia; Khan, Aamer; Fazid, Sheraz; Noor, Mohammad; Yousafzai, Yasar Mehmood; Sherin, Akhtar (Journal of Ayub Medical College Abbottabad, 2021)
Little is known about the pathophysiology and immunology of Severe Acute Respiratory Syndrome Corona Virus-2 (SARS-CoV-2). It is not yet clear whether SARS-CoV-2 infection produces long-term immune protection, or a short-lived immunity that would fade with the passage of time. We report a first case of SARS-CoV-2 reinfection in second wave from Pakistan. A 41-year-old male, health care worker developed flu-like illness, tested positive on 6th June 2020 and became PCR negative on 19th June 2020 with reactive antibodies. After 4 months and 13 days of negative PCR, he developed symptoms again and tested positive for SARS-CoV-2 with non-reactive antibodies. Keywords: SARS-CoV-2; COVID-19; Reinfection; Pakistan